In Silico Evaluation of Ciplukan (Physalis angulata Linn.) Compounds as Potential Serotonin Reuptake Inhibitors for Antidepressant Development - Azki Alfazahrah; Alifda Nurhayati; Bianti Meylia Wijaya; Larasati Arum Sari; Nabila Dinar Wulan; Luthfi Ahmad Muchlashi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Starfruit (Averrhoa bilimbi L.) is not only a commonly consumed as a fruit but is also widely used in traditional medicine. The plant has long been utilized by the communities to help treat various ailments, including coughs and rectal inflammation. This study aimed to determine the total flavonoid content and antioxidant activity of the ethanol extracts of Averrhoa bilimbi leaves fractionated using n-hexane. The extraction process was carried out using the maceration method with 70% ethanol, followed by fractionation with 95% n-hexane to separate active compounds from the crude extract. The total flavonoid content in the n-hexane fraction of the ethanol extract was measured using a UV-Vis spectrophotometer at a wavelength of 229-230 nm, while antioxidant activity was evaluated using the DPPH method at 515 nm. The results showed that the total flavonoid content of the n-hexane fraction of the ethanol extract was 37.3 mgQE/g extract. The antioxidant activity test produced an IC50 value of 6.58 μg/mL, compared to a standard IC50 value of 2.45 μg/mL for Askorbat acid. These findings indicate that the n-hexane fraction of Averrhoa bilimbi leaves ethanol extract possesses very strong antioxidant properties.